Hidrogés de quitosana/PVA reticulados com glutaraldeído para adsorção de corantes - Savaris, Daniela Langaro (2021)
Currently, one of the major environmental problems is found in emerging contaminants such as dyes from food and textile industries, due to the large volume of effluents discharged into the aquatic environment. Thus, the removal of dyes is paramount for all the problems that can be generated and the adsorption stands out due to its operational feasibility and technical simplicity in the remediation of the problem. The hydrogel that is a three-dimensional polymeric network and can be used as an adsorbent due to its characteristics, especially those synthesized by polysaccharides such as chitosan that is natural and renewable and in addition to combining with other polymers such as PVA, improving their mechanical properties. Thus, chitosan/PVA hydrogels were developed in different concentrations of acetic acid between 1.0 and 90 % to solubilize the chitosan, and cross-linked with glutaraldehyde in different concentrations to verify the adsorption capacity of these materials. The dye studied was erythrosine, and the hydrogel cross-linked with 1.0 % glutaraldehyde was used and a reduction of adsorption was observed as a function of time at different temperatures in the dye solution. Applying the mathematical kinetic models, at 25 and 35 ºC the best model was the pseudo first order model, which also fitted well to the hydrogel with 90% acetic acid at 25 ºC. For the study at 40 ºC it fit best the pseudo first and second order models. In the adsorption equilibrium study with hydrogel synthesized with 90 % acetic acid, the isotherms were applied and the model that best fitted was the Freundlich model.